THE INFLUENCE OF SUPERPLASTICISER ON THE DURABILITY PERFORMANCE OF CONCRETE IN AGGRESSIVE ENVIRONMENT - Ikumapayi, Catherine Mayowa; Ajayi, Joseph Adeniyi; Oyedepo, Olugbenga (Journal of Science, Technology and Innovation Research, 2026)
Concrete is one of the most versatile and widely used construction materials on earth. The use of superplasticizer as a chemical additive in concrete has recently attracted a lot of attention. However, chemical admixtures are often added to concrete to make high performance concrete. According to earlier studies, the use of chemical admixtures gives concrete advantageous properties both when it is fresh and when it has hardened. In this study, the impacts of superplasticizers (Costamix 200) at various dosages of 0, 1.2, 1.4, 1.6, 1.8, and 2.0 percentage are examined in relation to the mechanical properties and durability performance of concrete after a 28-day curing period in sodium chloride solution. The results of the experimental tests on Grade 20 concrete in both its fresh and hardened states are examined, and they are juxtaposed with the control sample. To assess the concrete's strength and durability, tests for water absorption, thermal conductivity, and compressive strength were performed. For dosages of 0% (control), 1.2%, 1.4%, 1.6%, 1.8%, and 2.0% of Costamix 200 superplasticizer, the compressive strength values were measured as follows: 26.88MPa, 28.40MPa, 28.66MPa, 29.02MPa, 29.4MPa, and 25MPa. The results show that increasing the dosage of the superplasticizer (Costamix 200) from 1.2% to 1.8% increased the compressive strength. The resistance of the resulting concrete to thermal conductivity and water absorption was also improved by the addition of the superplasticizer.